IMPROVING CHILDREN'S FINE MOTOR SKILLS THROUGH CUTTING ACTIVITIES IN GROUP A AT TK AMANAH MANDIRI MATTIRO DECENG - Ahmad Maududi; Suriani (Formad English Foundation NTB-Jakarta, 2024)
This study aims to develop fine motor skills in early childhood through cutting activities. Cutting activities are beneficial for training eye-hand coordination, hand muscle strength, and concentration. While cutting, children's fingers move according to the shapes being cut, which helps prepare them for writing, particularly in pencil grip. This research employs a Classroom Action Research (CAR) methodology consisting of two cycles: Cycle I and Cycle II. Each cycle involves several stages, including planning, implementation, observation, and reflection. The study was motivated by the fact that 7 out of 10 children in Group A at TK Amanah Mandiri Mattiro Deceng experienced difficulties in cutting activities. The subjects of this study were 10 children aged 4 to 5 years in Group A at TK Amanah Mandiri Mattiro Deceng. The data collection techniques used in this study included observation through direct monitoring, performance evaluation, and documentation. Improvement in children's fine motor skills was measured based on their accuracy in cutting according to patterns. The improvement was evident from the initial condition, where the average performance was 50%, increasing to 78% in Cycle I and reaching 85% in Cycle II. The findings of this research indicate that cutting activities effectively enhance the fine motor skills of children in Group A at TK Amanah Mandiri Mattiro Deceng in 2024.